(untitled) (Anclajes, 2014)
In the novel Las cartas que no llegaron by Mauricio Rosencof (2000) the experience of violent historical processes is the starting point of an exercise of memory retrieval in the form of writing letters. Interrogated by the traumatic experience, the narrator´s recollecting narrative goes into an exploration of frontiers, probing limits, fractures, thresholds, intersections, spaces of encounter. In this sense, the concept of frontier in its multiplicity and complexity is a heuristic key that permits to go through the text, to articulate it and to give account of its formal and thematic features.